Jurisdiction of Cases on Contesting Normative Legal Acts - Yushchenko, Natalya (Research Papers, 2018)
The aim of the article is to give the assessment of the current legislation on the questions connected with determination of jurisdiction and cognizance of cases of contest of regulatory legal acts is set. Based on the analysis of court practice of the Supreme Court of the Russian Federation, courts of law and Intellectual Property Rights Court the author draws the conclusions dealing with administrative legal proceedings, but also with special procedures of the arbitration legal proceedings.